Beyond Social Norms: Psychological and Hedonic Drivers of Metaverse Adoption Among Generation Y - Agnieszka Maria Koziel; Chien-Wen Shen; Irfandi Djailani; Yen-Ling Chang (IEEE Access)
The Metaverse has rapidly emerged as a transformative technological frontier, accelerated by key events such as the COVID-19 pandemic and Facebook’s rebranding as Meta. However, the factors influencing Generation Y’s adoption of Metaverse services remain underexplored. This study investigates the psychological, motivational, and social drivers shaping Generation Y’s adoption intentions, positioning the Metaverse as a bridge between the pre-digital and post-digital eras. Applying the Decomposed Theory of Planned Behavior, the findings reveal that perceived behavioral control and attitude significantly influence adoption, highlighting the roles of self-efficacy, user confidence, and positive perceptions of the technology. In contrast, subjective norms, central to traditional adoption models, exert no significant effect, suggesting a generational shift toward digital autonomy. Based on a survey of 341 Generation Y respondents in Taiwan, the findings provide practical insights for developers to prioritize user-friendly interfaces, immersive features, and customization options. Marketers are advised to leverage influencer-driven strategies and personalized digital interactions. The research contributes to theoretical advancements by challenging established models, such as the Unified Theory of Acceptance and Use of Technology, and calls for further research on cross-cultural differences and digital communities.